THE NEGATIVE IMPACT OF SOCIAL-POLITICAL ELITE TRANSACTIONS ON LOCAL DEMOCRACY IN GORONTALO - Apris Ara Tilome (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Democracy, as an ideal political system, is expected to ensure active public participation in the process of public decision-making. However, in the Indonesian context, the quality of local democracy is often distorted by transactional practices and the pragmatism of political elites. This phenomenon threatens the integrity of democracy, diminishes the quality of public participation, reinforces societal dependence on elites, and weakens democratic institutions. In Gorontalo, the practice of social transactions between political elites and the public has intensified, particularly during local elections and legislative campaigns. The case of the 2024 repeat voting (PSU) in the North Gorontalo Regency serves as a clear indication of the dominance of capital power and elite networks over candidates’ visions and missions. This study aims to analyze the negative impact of social-political elite transactions on local democracy and to formulate policy recommendations for strengthening a healthy, participatory, and integrity-based democratic system. The research adopts a quantitative approach using a survey design. The study population includes the general public, political elites, party officials, and election management and supervisory bodies (KPU, Bawaslu, and DKPP) across three regencies in Gorontalo Province. The findings reveal that transactional political practices are a defining feature of every electoral moment in the region, especially in the lead-up to regional and legislative elections. These transactions include money politics, short-term social assistance, and project promises in exchange for electoral support. This highlights how political contestation is largely determined by financial capital rather than candidate vision or integrity. Spearman correlation tests indicate a significant negative relationship between the intensity of social-political transactions and the quality of healthy political participation (r = -0.642; p < 0.01). The higher the transaction intensity, the lower the quality of participation and public trust in local democracy. These findings strengthen the hypothesis that local democracy in Gorontalo is regressing due to transactional politics. Without knowledge-based and policy-oriented interventions, the negative consequences are likely to persist, including the erosion of local government legitimacy, declining public trust in electoral institutions, and the loss of the substantive meaning of political participation as a form of public control over power.